The early promoters of bacteriophage HK022: contrasts and similarities to other lambdoid phages. - Cam, K M (1991)
The pL, pR and pM promoters of lambdoid phages direct the transcription of early phage genes and the prophage repressor gene. We have determined the start points of transcription for these three promoters in the lambdoid phage HK022 and have shown that the HK022 repressor represses the early promoters, pL and pR, and activates the repressor promoter, pM. HK022 resembles other phages of the lambda family in these respects, as it does in the functional organization of most of its early genes and sites. One exception is nun, the first gene of the HK022 pL operon, which is expressed in the presence of prophage repressor and thus differs from its lambda counterpart, gene N. We show that transcription of nun in a lysogen does not initiate at pL but instead starts upstream at the pM promoter. This difference in transcription fits the different roles of Nun and N proteins in the physiology of the two phages: Nun protects HK022 lysogens against superinfection with certain other lambdoid phages, while N promotes the transcription of early lambda genes.